2015
DOI: 10.1158/0008-5472.can-14-2921
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Derived Inflammatory Responses Accelerate the Formation of Immunosuppressive Myeloid Cells in the Tissue Microenvironment of Human Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic malignancies. PDAC builds a tumor microenvironment that plays critical roles in tumor progression and metastasis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 51 publications
10
92
0
Order By: Relevance
“…In mouse model studies, paclitaxel and doxorubicin treatments have been reported to increase the recruitment of TAMs in PyMT-MMTV mammary carcinoma, which then induces the treatment resistance [87,88]. Similarly, gemcitabine treatment recruits more TAMs into TME with immune suppressive functions in mouse pancreatic cancer model [89]. It has also been shown recently that chemotherapy agents, such as paclitaxel and cisplatin, remodel TME by inducing Jagged1 expression in osteoblasts and mesenchymal stem cells, which feeds back to tumor cells to activate Notch signaling and promotes chemo-resistance [90].…”
Section: Chemo-and Radiotherapiesmentioning
confidence: 99%
“…In mouse model studies, paclitaxel and doxorubicin treatments have been reported to increase the recruitment of TAMs in PyMT-MMTV mammary carcinoma, which then induces the treatment resistance [87,88]. Similarly, gemcitabine treatment recruits more TAMs into TME with immune suppressive functions in mouse pancreatic cancer model [89]. It has also been shown recently that chemotherapy agents, such as paclitaxel and cisplatin, remodel TME by inducing Jagged1 expression in osteoblasts and mesenchymal stem cells, which feeds back to tumor cells to activate Notch signaling and promotes chemo-resistance [90].…”
Section: Chemo-and Radiotherapiesmentioning
confidence: 99%
“…NSG or NRG mice that lack B and T cells as well as interleukin 2 receptor gamma) 55–57 . These host deficiencies substantially increase the engraftment rate at the expense of functional immunity, which is an important consideration in defining response to therapy 3,4,58 . To address this shortcoming, co-engraftment of the patient’s hematopoietic stem cells can reconstitute a more relevant immune contexture and perhaps more accurately model the disease 5963 .…”
Section: Pancreas Cancer Modelsmentioning
confidence: 99%
“…Another possibility is that the tumor-infiltrating T cells are kept at bay by co-infiltrating suppressive myeloid cells, present in great numbers in ovarian cancer and PDA (41)(42)(43)(44). It is still unclear how all the effects of the tumor microenvironment act in concert on the adaptive immune response to tumors, and therefore much work is yet to be done.…”
Section: Cautionary Tails: Limitations Of Mouse Models In Predicting mentioning
confidence: 99%